Factors Impacting HIV Pre-Exposure Prophylaxis Uptake and Coverage Among At-Risk Populations in West Africa: A Scoping Review - Cudjoe , Julius; Atatsi , Wisdom Kwabla (My University, 2024)
Introduction: Various PrEP projects and studies have been centered in Western Africa, as a result of high incidence of HIV in recent times, which explore various facets needed to be looked at in improving PrEP uptake and coverage particularly among high-risk populations, a key measure in helping to fight the HIV pandemic. Objectives: This scoping review explores available evidence, outlining the factors and affecting HIV PrEP uptake and coverage among vulnerable and key populations in West Africa. Methodology: This study adopted Arksey and O'Malley's (2005) scoping review framework for conducting the scoping review. A search was conducted on four digital databases – Scopus, ScienceDirect, PubMed, and Google Scholar - from January 2013 to December 2023. The PRISMA flow diagram was utilized and data were analyzed through thematic content analysis, following the socio-ecological model. Results: Thirty-seven studies were included in this review that met the eligibility criteria. 24 of these studies were conducted among MSM and 12 were conducted among FSW. 12 and 10 of the 37 studies reported on PrEP awareness and knowledge respectively. Awareness as reported by these studies was generally low among high-risk populations, however, 17 of the 37 studies reported high willingness and intention to take up PrEP following its introduction and education. From the study, facilitating factors that helped increase the uptake and usage of PrEP in the study were individual facilitators such as perception of high risk, having a good understanding of PrEP and HIV interpersonal factors such as peer education and support, and environmental factors like convenient access to PrEP and services tailored for at-risk populations. Barriers to PrEP included personal obstacles like money issues and socioeconomic uncertainties, as well as social barriers like stigma and the belief that taking PrEP means having HIV, and environmental barriers logistical constraints in providing services, stigma, and lack of healthcare setting motivation. Conclusion: PrEP as a preventive tool holds much promise in the fight against HIV, however, high- risk populations in West Africa for whom PrEP is mainly intended for still demonstrate low level of awareness and knowledge with various barriers to its use accounting for this. Therefore, in order to encourage facilitators and address barriers to PrEP uptake and usage, it is necessary to expand PrEP sensitization programs and tailor PrEP delivery services.
Mapping Out Factors Affecting HIV Pre-Exposure Prophylaxis Uptake and Coverage in West Africa
Keywords: HIV; Pre-Exposure Prophylaxis; PrEP; High-Risk Populations; West Africa